Researching trends in pemphigoid diseases: A bibliometric study of the top 100 most cited publications - Huang, Shih-Cheng; Chiu, Tsu-Man; Lee, Chien-Ying; Chang, Hui-Chin; Wu, Wen-Jun; Gau, Shuo-Yan (Frontiers in Medicine, 2023)
Background In the field of autoimmune and inflammatory disorders, different approaches were applied to provide information regarding disease activity, comorbidities, epidemiological reports and risk factors. However, no previous studies had thoroughly analyzed the research trend in the field, and the bibliometric analysis focusing on pemphigoid diseases was available. The objective of the current study was to evaluate the current research trend in the field. Methods A search has been conducted for the Web of Science database based on various subcategories of pemphigoid diseases. Detailed information including articles’ Publication types, Author information, Citation and publication information was attained for further analysis. Results Within the 6,995 studies, the top 100 most-cited articles were extracted for analysis. Among the top 100 studies, 70% of the studies focused on bullous pemphigoid. More than 60% of the top 100 studies were studies with original data. Furthermore, 30% of the studies were guidelines and narrative reviews. For the issues primarily focused on, most of the high-impact studies described the molecular mechanism of pemphigoid diseases (26%), managements (19%), risk factors of pemphigoid diseases (17%). Additionally, some other studies provided general review or discussed about the issue of epidemiology, diagnosis/definition, comorbidities and clinical characteristics of pemphigoid diseases. Conclusions This comprehensive bibliographic study of pemphigoid diseases provided an overview of current research focuses in the field. Topics such as disease management, molecular mechanism of pathogenesis, and drug-inducing pemphigoid diseases were highly mentioned in the most-cited studies. For researchers and clinicians, the researching trend and study focus in the top-100 cited studies could serve as a potential reference for future investigation and patient management.